Creative science : achieving the WOW factor with 5-11 year olds - Feasey, Rosemary (David Fulton, 2005)
Through a refreshing blend of theory and practice this book provides stimulating material to develop creative approaches to science in the classroom. It includes:a range of teaching approaches that relate directly to the topic under discussionexamples of pupils' work that portray how theory can be translated into practicequick off-the-shelf example model lesson plans which can be adapted. User-friendly and clearly laid out this book is a core text for primary teachers, NQTs and students who want to inject some creativity into their teaching and put.